Whole Genome-Based Amplified Fragment Length Polymorphism Analysis Reveals Genetic Diversity in Candida africana - Chowdhary, Anuradha; Hagen, Ferry; Sharma, Cheshta; Al-Hatmi, Abdullah M. S.; Giuffrè, Letterio; Giosa, Domenico; Fan, Shangrong; Badali, Hamid; Felice, Maria Rosa; de Hoog, Sybren; Meis, Jacques F.; Romeo, Orazio (Frontiers in Microbiology, 2017)
This study aimed at investigating the genetic diversity of a panel of Candida africana strains recovered from vaginal samples in different countries. All fungal strains were heterozygous at the mating type-like locus and belonged to the genotype A of Candida albicans. Moreover, all examined C. africana strains lack N-acetylglucosamine assimilation and sequence analysis of the HXK1 gene showed a distinctive polymorphism that impair the utilization of this aminosugar in this yeast. Multilocus sequencing of seven housekeeping genes revealed a substantial genetic homogeneity among the strains, except for the CaMPIb and VPS13 loci which contributed significantly to the classification of our set of C. africana strains into 6 existing diploid sequence types. Amplified fragment length polymorphism (AFLP) fingerprint analysis yielded greater genotypic heterogeneity among the C. africana strains. Overall the data reported here show that in C. africana genetic diversity occurs and the existence of this intriguing group of C. albicans strains with specific phenotypes associated could be useful for future comparative studies in order to better understand the genetics and evolution of this important human pathogen.